Occurrence and distribution of juveniles of Mcicrobrachium rosenbergii (de Man) in the mangrove soil from Cochin backwaters, Kerala - R, Sunil Kumar (Indian Journal of Fisheries, 2011)
The occurrence and distribution of juveniles oi Macrobrachium rosenbergii, acommerciallj’ important fresh water prawn, in the mangrove ecosystem of Cochinbackwaters are described. Maximum density of this species was found more inthe unconsolidated and semi-fluid mangrove soil of low tide zone than the littleconsolidated substratum of high tide zone. The juveniles were found up to 15 cmdepth in the soil. Overall, this species showed an inconsistent pattern in densityand distribution both horizontally and vertically in the mangrove soil of thelittoral zone.